2016
DOI: 10.1007/s12035-016-0128-4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Biomarkers in the Diagnosis of Creutzfeldt-Jakob Disease in Slovak Patients: over 10-Year Period Review

Abstract: Creutzfeldt-Jakob disease is a rare, but rapidly progressive, up to now untreatable and fatal neurodegenerative disorder. Clinical diagnosis of Creutzfeldt-Jakob disease (CJD) is difficult; however, it can be facilitated by suitable biomarkers. Aim of the present study is to compare levels of cerebrospinal fluid biomarkers (total tau protein, phosphorylated-tau protein, protein 14-3-3 and amyloid beta) in Slovak population of CJD suspect cases, retrospectively in over a 10-year period. One thousand three hundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The diagnostic accuracy of MDH1 in gCJD is comparable to sCJD (specificity of 85% and a sensitivity of 83%) [22]. In the context of other surrogate biomarkers, such as 14-3-3, the sensitivity to diagnose E200K was indicated between 77 and 89% [32][33][34]. In addition, our recent study on alpha-synuclein using an electro-chemiluminescent assay based on the Meso Scale Discovery (MSD) technology, revealed a diagnostic accuracy for gCJD E200K of 0.96 AUC and for FFI of 0.75 AUC [35] which is higher than MDH1 detection.…”
Section: Discussionmentioning
confidence: 91%
“…The diagnostic accuracy of MDH1 in gCJD is comparable to sCJD (specificity of 85% and a sensitivity of 83%) [22]. In the context of other surrogate biomarkers, such as 14-3-3, the sensitivity to diagnose E200K was indicated between 77 and 89% [32][33][34]. In addition, our recent study on alpha-synuclein using an electro-chemiluminescent assay based on the Meso Scale Discovery (MSD) technology, revealed a diagnostic accuracy for gCJD E200K of 0.96 AUC and for FFI of 0.75 AUC [35] which is higher than MDH1 detection.…”
Section: Discussionmentioning
confidence: 91%
“…In fact, soluble amyloid beta‐protein (Aβ) and apolipoprotein E levels in CSF are significantly lower in patients with definite Alzheimer's disease (AD) . Moreover, it has been shown that there is a substantial decrease in the levels of total secreted β‐amyloid precursor protein (sAPP), sAPP‐alpha (sAPPα) and Aβ in the CSF of normal pressure hydrocephalus (NPH) patients who may develop AD‐like pathology . However, CSF contains only a small portion of the metabolites in the brain and thus is a great limitation to accurately reflecting the pathophysiological status of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the brain, the blood–brain barrier (BBB), which separates circulating blood cells and solutes from the brain parenchyma and ISF , makes venous blood in the brain only a component of micromolecular metabolites. Thus, CSF, instead of venous blood in the brain, has been widely considered a major diagnostic target for brain diseases . Owing to the great permeability of lymphatic vessels, it is reasonable to hypothesize that there are more brain metabolites in BLF than in CSF, and brain metabolites in BLF vary dynamically and may reflect more accurate physiological and pathological conditions of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…A definitive diagnosis of sCJD requires histological analysis of brain tissues obtained during autopsy [3], but it cannot always clinically distinguish CJD from other rapidly progressive neurodegenerative disorders in living patients, since these diseases share several clinical characteristics [4][5][6]. Therefore, there has been extensive research effort devoted to identifying cerebrospinal fluid (CSF) protein biomarkers for the premortem diagnosis of sCJD [7][8][9][10]. Indeed, diagnosis using CSF biomarkers has shown several benefits of reducing the diagnostic turn-around time with reproducible data without any risk of damage to the patient's brain.…”
Section: Introductionmentioning
confidence: 99%